The Application of AI in Clinical Nursing, Yields Several Advantageous Outcomes - Ahmed, Habib; Akber , Naeema; Saleem, Mohammad; Ahmed, Faheem; Yasmeen, Rifat; Ali, Liaquat (Indus Journal of Bioscience Research, 2025)
AI applications in nursing practice deliver transformative improvements for patient care while reducing workflow disruptions and serving healthcare workers better. This research explores how AI helps nursing professionals through clinical decision systems as well as patient observation and workload optimization and mental health resource delivery. Through their integration of clinical decision support tools and predictive analytics along with automation technologies healthcare professionals experience better efficiency together with lower administrative burdens and improved patient safety. The use of AI in mental health support delivers individualized tools to nurses that enable them to protect themselves from burnout and stress. The adoption of AI technology faces crucial ethical obstacles that include privacy risks related to patient information and systemic bias within algorithms and social repercussions of their deployment. The complete benefits of AI in nursing depend on an equilibrium between technological progress and patient-focused care approaches. The future success of healthcare professionals depends on the integration of AI education into nursing curricula for their preparation in AI-driven health environments. The research demonstrates how AI technology enables nursing practice transformation but calls for ethical monitoring practices and continuous assessment to produce fair and effective deployment outcomes.